1999
DOI: 10.1523/jneurosci.19-06-02069.1999
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sorting of Nerve Growth Factor and Brain-Derived Neurotrophic Factor in Hippocampal Neurons

Abstract: Nerve growth factor (NGF) is released through the constitutive secretory pathway from cells in peripheral tissues and nerves where it can act as a target-derived survival factor. In contrast, brain-derived neurotrophic factor (BDNF) appears to be processed in the regulated secretory pathway of brain neurons and secreted in an activity-dependent manner to play a role in synaptic plasticity. To determine whether sorting differences are intrinsic to the neurotrophins or reflect differences between cell types, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
241
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 300 publications
(259 citation statements)
references
References 54 publications
(72 reference statements)
16
241
0
2
Order By: Relevance
“…36 The entorhinal cortex is the earliest cortical region affected by AD (stages I/II), followed by the hippocampus (stages III/IV). 20 In our study we observed a clear augmentation in the levels of nonenzymatic oxidative modifications in pro-NGF molecules in hippocampus and entorhinal cortex samples from AD-affected brains. This increase is present for both lipoxidation and glycoxidation.…”
Section: Discussionsupporting
confidence: 55%
“…36 The entorhinal cortex is the earliest cortical region affected by AD (stages I/II), followed by the hippocampus (stages III/IV). 20 In our study we observed a clear augmentation in the levels of nonenzymatic oxidative modifications in pro-NGF molecules in hippocampus and entorhinal cortex samples from AD-affected brains. This increase is present for both lipoxidation and glycoxidation.…”
Section: Discussionsupporting
confidence: 55%
“…These apparent discrepancies in the time course of BDNF secretion could reflect differences in the sorting and release of native BDNF, AdVBDNF, and BDNF-GFP (cf. Fawcett et al, 1997; Mowla et al, 1999) or other differences among the models used in these three studies.…”
Section: Discussionmentioning
confidence: 97%
“…Synthesized as a precursor, proBDNF is then sorted into one of the two secretory pathways: constitutive (passive) or regulated (induced or active) (4)(5)(6). Until recently, only mature BDNF (mBDNF) was considered biologically active.…”
mentioning
confidence: 99%